Inggris Inggris - Sohdi, Lalu Rahmat (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2024)
This comprehensive study aims to determine how much growth rates, profitability, liquidity, and corporate valuation influence company stock prices listed on the LQ45 index for the 2019-2021 period. The data used in this study is secondary data. The research sample was meticulously selected using a purposive sampling technique so that 34 companies were obtained with 102 samples. The results showed that simultaneously all the variables used, namely: X1_Sustainability Growth Rate, X2_Return on Assets (ROA), X3: Quick Ratio (QR), X4_Price to Book Value (PBV), and X5: Price Earning Ratio (PER) have no effect which is significant to the dependent variable, namely stock prices. However, partially, it was found that the variable X3_Quick Ratio has a significant negative effect on stock prices. However, the other four variables do not significantly affect the dependent variable, namely stock prices. This may be due to this study's significant presence of confounding variables.